Impact of Virtual Reality on Learning Complex Biological Processes: A Study of Secondary Schools in Delta State, Nigeria - Chukwuka Rita Ewere (Universitas Negeri Makassar, 2025)
Advances in educational technology have created new opportunities for enhancing science learning. Virtual reality (VR) offers immersive and interactive experiences that may improve students’ conceptual understanding and practical skills in biology, particularly in complex topics such as cellular respiration, mitosis, and enzyme action. This study employs a quasi-experimental non-equivalent control group pretest-posttest design. A sample of 120 Senior Secondary School Two (SSS II) biology students will be drawn from four schools in Delta State, Nigeria, representing both urban and rural settings. Two schools will be assigned as experimental groups receiving VR-based instruction, while two will serve as control groups taught using conventional lecture, chalkboard, and textbook methods. Data collection will utilize two validated and reliable instruments: the Biology Conceptual Understanding Test (BCUT) and the Biology Practical Skills Performance Test (BPSPT). The intervention spans six weeks, with both groups completing pre-tests and post-tests. Data will be analyzed using descriptive statistics and Analysis of Covariance (ANCOVA) to compare outcomes while controlling for baseline scores. It is expected that students exposed to VR-based instruction will demonstrate significantly higher gains in conceptual understanding and practical performance than those taught with conventional methods. Findings will provide empirical evidence on the effectiveness of VR in secondary school biology education in Nigeria. The study highlights the potential of immersive technologies to strengthen science teaching and learning, with implications for curriculum innovation in developing contexts.